SUPERVISION OF MUSEUM ACTIVITY - Rafał Golat (Index Copernicus International S.A., 2021)
Supervision of museums should be perceived taking into account both specific regulations: addressed directly to museums, particularly in the Act on Museums, as well as general regulations assuming supervision mechanisms in different respects, e.g., construction process or HR. This complex perspective: systemic and normative, is essential not only with respect to the supervision in a narrow basic meaning of the term, associated in the first place with an inspection of the supervised entity and application of respective executive actions, e.g., undertaken in the form of administrative decisions, but also the supervision in a broader perspective, understood as a whole range of support provided to a museum, including issuing recommendations, evaluations, and opinions important for its operation. In the context of ‘external’ supervision implemented by appropriate organs and entities, the following are of basic importance: the museum’s organiser (founder) supervision, constituting one of the organiser’s basic statutory responsibilities, as well as the supervision of the minister responsible for culture and preservation of national heritage, with respect to e.g., the preservation and care of historic monuments and museum operations; additionally, it is the matter of conservation supervision performed by Voivodeship Conservators of Historic Monuments as organs specialized in the preservation and care of historic monuments, the latter constituting, e.g., museum collections. As for the ‘internal’ supervision aspects, the role of museum councils, obligatory in public museums (state ones or organised by local governments), needs to be emphasized. Their statutory responsibility is to e.g., supervise how museums fulfil their responsibilities with respect to the collection and the public, in particular how they fulfil the goals as specified in Art.1 of the Act on Museums. The questions of supervision are also important for non-public museums (their founders) which in the event of violating either the Act’s provisions or their own charter have to be prepared that supervisory activities might be applied to them, up to the ban on their further operations.